FoxO3 Modulates LPS-Activated Hepatic Inflammation in Turbot (Scophthalmus maximus L.) - Pan, Mingzhu; Liu, Jiahuan; Huang, Dong; Guo, Yanlin; Luo, Kai; Yang, Mengxi; Gao, Weihua; Xu, Qiaoqing; Zhang, Wenbing; Mai, Kangsen (Frontiers in Immunology, 2021)
Forkhead box O3 (foxo3) plays important roles in immune system. The present study characterized the foxo3 in turbot (Scophthalmus maximus L.). Lipopolysaccharide (LPS) incubating in vitro and injecting in vivo were used to construct inflammatory models. The foxo3 was interfered and overexpressed to investigate its functions in inflammation. Results showed that the open reading frame of foxo3 was 1998 bp. Tissue distribution analysis revealed that the highest expression of foxo3 was in muscle. Immunofluorescence result showed that foxo3 expressed in cytoplasm and nucleus. Knockdown of foxo3 significantly increased mRNA levels of tumor necrosis factor-α (tnf-α), interleukin-1β (il-1β), interleukin-6 (il-6), myeloid-differentiation factor 88 (myd88), cd83, toll-like receptor 2 (tlr-2) and protein level of c-Jun N-terminal kinase (JNK) in sifoxo3 + LPS (siRNA of foxo3+ LPS) group compared with NC + LPS (negative control + LPS) group. Overexpressed foxo3 significantly decreased mRNA levels of tnf-α, il-6, nuclear transcription factor-kappa B (nf-κb), cd83, tlr-2 and the protein level of JNK in vitro. In vivo analysis, foxo3 knockdown significantly increased levels of GOT in serum after LPS incubation compared with NC+LPS group. Overexpressed foxo3 significantly decreased levels of GPT and GOT in pcDNA3.1-foxo3+LPS group compared with pcDNA3.1+LPS group. Foxo3 knockdown significantly increased mRNA levels of tnf-α, il-1β, il-6, nf-κb, myd88 and protein level of JNK in vivo in NC+LPS group compared with sifoxo3+LPS group. Overexpressed foxo3 significantly decreased mRNA levels of il-1β, il-6, myd88, cd83, jnk and protein level of JNK in pcDNA3.1-foxo3+LPS group compared with pcDNA3.1+LPS group. Hence, foxo3 modulates LPS-activated hepatic inflammation in turbot.